The Syuro-Participative Leadership in Al-Qur’an-Based Pesantren in the Disruption Era - Muh. Mustakim; Ahmad Salim; Kana Safrina Rouzi; Ruwet Rusiyono; Desy Khusna Nurmaida (Ta'dib, 2021)
This study discussed the renewal of leadership models in Al-Qur'an-based pesantren. Leadership in pesantren has a major influence on its development and existence. Ibn Abbas Islamic Boarding School is interesting to study because it is modern managed. This is a case study to examine in depth the developed leadership model. The data were collected through observation, documentation, and interview, and analyzed using the Miles Huberman triangulation model, so that the results were in the form of abstractions showing their novelty. Pesantren Ibnu Abbas Klaten is led by a director who acted as a manager as well as mufti and kyai. The director supervises three educational units; the pesantren, the santri, and the school unit, which each led by a chief. Even though a director (or Kyai) has full leadership rights, the "syuro-participative" leadership model is implemented in regular meetings every week, and the deliberation results showing the participation of each existing institution. This indicated that the highest forum is at the leadership meeting, not unilaterally by the Kyai.